Clinical analysis of 42 cases of vesicoureteric reflux in children - ZHANG Lin; ZHAO Li-ping; ZHOU Hong-xia; GE Ting-ting (Linchuang shenzangbing zazhi, 2015)
Objective To review retrospectively the clinical data,renal damage and prognosis of vesicoureteral reflux（VUR） in children,hoping to give more attention to early recognition and treatment of the disease.Methods Forty-two children with VUR who were hospitalized from January 2010 to December 2012 were studied,of whom the VUR grades,renal scar development,and prognosis of VUR were evaluated.Results The incidence of VUR in urinary tract infection（UIT） children was35.9%（42/117）,while the proportion of VUR in recurrent UIT group was 62.2%,significantly higher than that in first UIT group（23.7%）.In different age groups,the incidence of VUR in infants was the highest（61.9%）,and that of severe reflux（grades Ⅳ-Ⅴ） was 48.6%.Only 20 children with VUR had complete follow-up data,including 2 cases of mild reflux（grade Ⅰ-Ⅱ）,7 cases of moderate reflux（grade Ⅲ） and 11 cases of severe reflux（grade Ⅳ-Ⅴ）.The average interval of repeated micturating cystourethrography（MCU） was 1-2 years.After follow-up,it was found that the reflux grade had different degrees in changes:complete remission in 3 cases,partial remission in 6 cases,no change in 10 cases,and worse situation in 1 case.There were 7 cases of renal scarring,all of which occurred in moderate and severe reflux.Six children with renal scar were younger than two years.Five cases were diagnosed in the first 99mTc-dimercaptosuccinic acid（DMSA） examination,and2 were found during the follow-up process.Of 42 children with VUR,2 cases received surgical treatment after the definite diagnosis,and 40 cases were given internal medicine（in 20 cases having complete follow-up data,2 cases received surgical treatment）.Conclusions Children with VUR need early diagnosis and treatment,especially for infants.It is necessary to evaluate renal damage timely,and reasonably adjust the treatment plan.Efforts should be made to strengthen education,conduct good long-term follow-up and normal therapy,so that we will effectively protect the renal fuction.